Commensal Streptococcus mitis produces two different lipoteichoic acids of type I and type IV. (26th July 2021) - Gisch, Nicolas; Peters, Katharina; Thomsen, Simone; Vollmer, Waldemar; Schwudke, Dominik; Denapaite, Dalia
Abstract: The opportunistic pathogen Streptococcus mitis possesses, like other members of the Mitis group of viridans streptococci, phosphorylcholine ( P -Cho)-containing teichoic acids (TAs) in its cell wall. Bioinformatic analyses predicted the presence of TAs that are almost identical with those identified in the pathogen Streptococcus pneumoniae, but a detailed analysis of S. mitis lipoteichoic acid (LTA) was not performed to date. Here, we determined the structures of LTA from two S. mitis strains, the high-level beta-lactam and multiple antibiotic resistant strain B6 and the penicillin-sensitive strain NCTC10712. In agreement with bioinformatic predictions, we found that the structure of one LTA (type IV) was like pneumococcal LTA, except the exchange of a glucose moiety with a galactose within the repeating units. Further genome comparisons suggested that the majority of S. mitis strains should contain the same type IV LTA as S. pneumoniae, providing a more complete understanding of the biosynthesis of these P -Cho-containing TAs in members of the Mitis group of streptococci. Remarkably, we observed besides type IV LTA, an additional polymer belonging to LTA type I in both investigated S. mitis strains. This LTA consists of β-galactofuranosyl-(1, 3)-diacylglycerol as glycolipid anchor and a poly-glycerol-phosphate chain at the O -6 position of the furanosidic galactose. Hence, these bacteria are capable of synthesizing two different LTA polymers, most likely produced by distinct biosynthesis pathways. Our bioinformatics analysis revealed the prevalence of the LTA synthase LtaS, most probably responsible for the second LTA version (type I), among S. mitis and Streptococcus pseudopneumoniae strains.